Ethnicity and Body Dissatisfaction Among Women in the United States A Meta-Analysis. [article]. - Grabe, Shelly
The prevailing view in popular culture and the psychological literaure is that White women have greater body dissatisfaction than women in color. In this meta-analysis, 6 main effects sizes were obtained for differences among Asian American, Black, Hispanic, and White women with a sample of 98 studies, yielding 222 effect sizes. The average d for the White-Black comparison was 0.29, indicating that White women are more dissatisfied, but the difference is small. All other comparisons were smaller, and many were close to zero. The findings directly challenge the belief that there are large differences in dissatisfaction may not be the golden girl problem promoted in the literature. Implications for theory and treatment are discussed. -- (from the author)